Deregulation of the endocannabinoid system and therapeutic potential of ABHD6 blockade in the cuprizone model of demyelination - Manterola, Andrea (Biochem Pharmacol, 2018)
Multiple sclerosis (MS) is a chronic demyelinating disease of unknown etiology in which tissue pathology suggests both immune-dependent attacks to oligodendroglia and primary oligodendrocyte demise. The endocannabinoid system has been crucially involved in the control of autoimmune demyelination and cannabinoid-based therapies exhibit therapeutic potential, but also limitations, in MS patients. In this context, growing evidence suggests that targeting the hydrolysis of the main endocannabinoid 2-arachidonoylglycerol (2-AG) may offer a more favorable benefit-to-risk balance in MS than existing cannabinoid medicines. Here we evaluated the modulation of endocannabinoid signaling and the therapeutic potential of targeting the 2-AG hydrolytic enzyme alpha/beta-hydrolase domain-containing 6 (ABHD6) in the cuprizone model of non-immune dependent demyelination. The concentrations of N-arachidonoylethanolamine (anandamide, AEA) and its congener N-palmitoylethanolamine (PEA) were reduced following 6 weeks of cuprizone feeding. Deregulation of AEA and PEA levels was not due to differences in the expression of the hydrolytic and biosynthetic enzymes fatty acid amide hydrolase and N-acylphosphatidylethanolamine-phospholipase D, respectively. Conversely, we measured elevated transcript levels of 2-AG hydrolytic enzymes monoacylglycerol lipase, ABHD6 and ABHD12 without changes in bulk 2-AG concentration. Upregulated CB(1) and CB(2) receptors expression, ascribed in part to microglia, was also detected in the brain of cuprizone-treated mice. Administration of an ABHD6 inhibitor partially attenuated myelin damage, astrogliosis and microglia/macrophage reactivity associated to cuprizone feeding. However, ABHD6 blockade was ineffective at engaging protective or differentiation promoting effects in oligodendrocyte cultures. These results show specific alterations of the endocannabinoid system and modest beneficial effects resulting from ABHD6 inactivation in a relevant model of primary demyelination.